2017
DOI: 10.1016/j.carrev.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-induced acute kidney injury in interventional cardiology: Emerging evidence and unifying mechanisms of protection by remote ischemic conditioning

Abstract: Contrast-induced acute kidney injury (CI-AKI) is a common complication of many diagnostic and therapeutic cardiovascular procedures. It is associated with longer in-hospital stay, more complicated hospitalization course, and higher in-hospital morbidity and mortality. With increasing use of contrast media in various diagnostic and interventional procedures, the prevalence of CI-AKI is expected to rise. Although pre-hydration with intravenous normal saline is recommended in patients with elevated risk of CI-AKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…The effects of remote ischemic conditioning have been investigated in IR scenarios of different organs (e.g. myocardium [ 23 , 24 ], brain [ 25 ], kidney [ 26 , 27 ], and by our group on liver [ 10 , 12 ]) in multiple experimental and clinical studies over the past years [ 9 ]. However, available and consistent datasets from well-designed and comprehensive experimental studies, which would demonstrate the effects of this approach in liver transplantation are rare ( Table 1 .)…”
Section: Discussionmentioning
confidence: 99%
“…The effects of remote ischemic conditioning have been investigated in IR scenarios of different organs (e.g. myocardium [ 23 , 24 ], brain [ 25 ], kidney [ 26 , 27 ], and by our group on liver [ 10 , 12 ]) in multiple experimental and clinical studies over the past years [ 9 ]. However, available and consistent datasets from well-designed and comprehensive experimental studies, which would demonstrate the effects of this approach in liver transplantation are rare ( Table 1 .)…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism behind the renal protection of RIPC is not clearly understood. However, it has been reported that RIPC can develop its effect on kidneys in two different ways; generating nitric oxide/nitrate and release of damage associate proteins, and inducing cell cycle arrest in kidneys (33). Nitric oxide generation and vasodilatation can prevent renal vasoconstriction, while damaged associate proteins will further prevent cell death and therefore prevent renal injury (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that RIPC can develop its effect on kidneys in two different ways; generating nitric oxide/nitrate and release of damage associate proteins, and inducing cell cycle arrest in kidneys (33). Nitric oxide generation and vasodilatation can prevent renal vasoconstriction, while damaged associate proteins will further prevent cell death and therefore prevent renal injury (33). Moreover, recent metaanalyses about the efficacy of RIPC has demonstrated that this intervention can reduce the incidence of AKI and MI in patients undergoing PCI (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…With the more and more common application of invasive diagnostic and treatment procedures, contrast‐induced nephropathy (CIN) has become an important cause of acute renal failure in current clinical practice . Generally, CIN is defined as a relative increment of serum creatinine (SCr) of more than 25% or an absolute increment of SCr of more than 0.5 mg (or 44.2 μmol/L) as compared with its baseline level within 48 or 72 hours after contrast exposure .…”
Section: Introductionmentioning
confidence: 99%